Corrigendum: Uncertainty in coprophilous fungal spore concentration estimates - Perrotti, Angelina G. (2023)
In the published article, there was an error in the Discussion section, page 5, first paragraph. The terms “over-reported” and “under-reported” were switched in the sentence, rendering it incorrect. The corrected sentence appears below: “Due to the asymmetrical uncertainty, we suggest that it is more likely CFS are over-reported than under-reported in studies with low total counts.” The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.